LoRa-based Smart Patient Monitoring System - Murdan, A.P.; Ramphul, J.S. (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2023)
Advancements in mobile technologies, internet, cloud computing, digital platforms and social media have significantly contributed to connecting people after the COVID-19 pandemic. With people becoming much more health-conscious, there is a growing demand for innovative ways to monitor health and well-being. This project aims at deploying Internet of Things (IoT) devices for measuring vital medical parameters of patients and securely transmitting the data to caregivers or any authorized persons for timely decisions. Essentially, our proposed system allows patients to move freely within a certain radius, while wearing an IoT kit, consisting of several sensors and communication modules. The project consists of three main parts: transmission, receiving and ‘body fall’ detection and alert systems. The transmission section records data through sensors and sends it to the receiving section, which then uploads the data to the cloud. The ‘body fall’ system detects changes in orientation and acceleration, alerting caregiver, in case the patient falls. Implementation and testing were successfully performed, with live data presented to caregivers through the LoRa technology and IoT platforms such as Blynk and Cayenne.